Double stage converter with low current stress for low to high voltage conversion in nanogrid. (November 2021) - Sadaf, Shima; Al-Emadi, Nasser; Iqbal, Atif; Bhaskar, Mahajan Sagar
Abstract: A low to high voltage conversion technique has been proposed in this paper using double stages of switched inductors for nanogrid applications. The proposed converter topology utilizes fewer components, achieves high voltage gain at a small value duty ratio, and has high efficiency. Moreover, the proposed converter provides a reduced switch current stress to obtain a stable constant boosted DC voltage. Therefore, it requires low-current rating switches and hence leads to cost reduction. Additionally, the load and the source end are connected to the same ground. The principle of operation, theoretical waveforms in Continuous Conduction Mode (CCM), and Discontinuous Conduction Mode (DCM) with steady-state analysis are discussed. A detailed discussion about the effect of non-idealities on the high voltage conversion, the design of components, and a comparison of the performance characteristics such as the number of components, Voltage Gain in CCM, switch current stress, normalized switch voltage stress, and efficiency of the proposed converter topology with other converters are presented. The experimental results of the 500W laboratory prototype are also shown to validate the operation of the proposed converter.